Basophilic green fluorescent carbon nanoparticles derived from benzoxazine for the detection of Cr(vi) in a strongly alkaline environment. Issue 14 (15th February 2018) - Fang, Bin; Wang, Ping; Zhu, Yujia; Wang, Caoyu; Zhang, Geng; Zheng, Xinsheng; Ding, Cong; Gu, Jiangjiang; Cao, Feifei
Abstract : Basophilic green fluorescent carbon nanoparticles (G-CNPs) were prepared from benzoxazine for the selective detection of Cr(vi ) in strongly alkaline environments. Abstract : Fluorescent probes for heavy or transition metal ions in extreme environments are crucially important for practical use. In this work, basophilic green fluorescent carbon nanoparticles (G-CNPs) were synthesized by one-pot hydrothermal treatment of benzoxazine in NaOH aqueous solution. These G-CNPs showed favorable dispersibility in strongly alkaline conditions due to the abundant functional groups on their surface. Based on their good photoluminescence properties and excellent stability, the G-CNPs could be used to detect Cr(vi ) in a strongly alkaline environment (pH = 14) through a fluorescence quenching effect. This detection process was achieved selectively among 17 anions within 30 seconds and the limitation was 0.58 μM (S/N = 3). It was revealed that the fluorescence turn-off process was caused by the inner filter effect (IFE) of Cr(vi ). This study developed efficient fluorescence sensors based on fluorescent carbon nanoparticles, which could be used in strongly alkaline environments.